Differential diagnoses of irritability and temper loss in a 6-year-old. (October 2022) - Fredrick, Joseph W; Rodriguez, Beatriz; Lynch, James D; Loren, Richard EA; Tamm, Leanne
Irritability and temper loss are common concerns among young children seen for mental health diagnostic evaluations and represent features of nearly a dozen childhood mental health conditions. Thus, careful assessment of irritability and temper loss is essential for informing case conceptualization, diagnosis, and treatment recommendations. The current case study provides a clinical description of a 6-year-old Black male ("Tyler") seen in a tertiary pediatric medical center for concerns related to significant inattention, hyperactivity, impulsivity, oppositional behaviors, irritability, and severe temper loss displayed at home and school. The clinical description summarizes findings from rating scales and diagnostic evaluations, case conceptualization, as well as treatment recommendations. Detailed suggestions for clinicians regarding strategies for assessing irritability and temper loss and questions to consider when seeking clarification to inform differential diagnoses are provided.